Aplikasi Informasi dan Pendaftaran Kegiatan Mahasiswa Universitas Kristen Petra Berbasis Android - Hengky Alexander Rustan; Henry Novianus Palit; Kristo Radion Purba (Jurnal Infra, 2017)
During this time, the process of publication of activities within the Institute of Student Affairs at Petra Christian University still use the manual that is in the form of posters that are printed and posted on bulletin boards. This resulted in not a few students who did not receive information publication of an activity if they are not actively see the posters posted on the bulletin board. And another reality, for the registration process participants still use the manual that is in the form of paper.Android based application of information and registration for students in Petra Christian University is made to assist student in receiving information of publication of an event activity in university scope and to assist student who is being the head of event activity in publicizing activity event which can reach as many students as possible. This program uses Firebase Cloud Messaging as a forum for delivering event activity information and also using Google Calendar as a reminder of events. So that with this application the student can receive information publication of an activity and register in the activity more easily and quickly.